IMPLEMENTASI PENDIDIKAN MORAL MELALUI IMTAQ OLEH GURU DALAM MEMBENTUK KARAKTER SISWA DI SMA NEGERI 1 DEDAI - Suparno, Suparno; Juri, Juri; Paulinus, Paulinus (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2023)
The faith and devotion of students is the goal of national education where school educational institutions are one of the most effective vehicles for achieving educational goals. However, the problem in the study of the implementation of moral education through faith and piety (imtaq) by teachers to shape the character of students at SMA Negeri 1 Dedai, the condition of moral behavior and personality of students is very concerned, this is indicated by the existence of cases such as students being late when the lesson starts, students do not pay attention to the teacher when delivering the material and there are many students who skip or run away during school hours. The purpose of the research is to describe the implementation of moral education through Imtaq by teachers to shape student character at SMA Negeri 1 Dedai. Researchers used qualitative methods, the subjects and objects of research were teachers of Islamic Religion, Catholic Religion and Islamic Religion Students and Catholic Religion Students. The data analysis technique used is a qualitative approach in this study, data collection techniques through observation, interviews (interviews), and documentation. The results showed that: (1) The purpose of the imtaq program at SMA Negeri 1 Dedai is to instill good character values in students, besides that it also familiarizes students so that students have faith and devotion to Allah SWT. (2) The implementation of the imtaq program in instilling student character at SMA Negeri 1 Dedai has been going well and with this imtaq program students have reflected good character. The conclusion is that the implementation of moral education through imtaq is very good for shaping student character.Â Keywords:Moral Education and Imtaq Â Â